2021
DOI: 10.3390/atmos12070927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Sowing Dates of Wheat under Arid and Semi-Arid Climatic Regions and Impact Quantification of Climate Change through Mechanistic Modeling with Evidence from Field

Abstract: Rising temperature from climate change is the most threatening factor worldwide for crop production. Sustainable wheat production is a challenge due to climate change and variability, which is ultimately a serious threat to food security in Pakistan. A series of field experiments were conducted during seasons 2013–2014 and 2014–2015 in the semi-arid (Faisalabad) and arid (Layyah) regions of Punjab-Pakistan. Three spring wheat genotypes were evaluated under eleven sowing dates from 16 October to 16 March, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Wheat is a major cereal crop of Pakistan and also important as a food crop (Ul Hassan et al 2021 ; Rahman et al 2021a ). It is grown in the areas that are affected by water shortage (Hussain et al 2021 ). Multan also includes in these regions where wheat crops face dry periods and fog is a common occurrence, especially during December, January, and February (Rahman et al 2018 , 2021b ; Ghafoor et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat is a major cereal crop of Pakistan and also important as a food crop (Ul Hassan et al 2021 ; Rahman et al 2021a ). It is grown in the areas that are affected by water shortage (Hussain et al 2021 ). Multan also includes in these regions where wheat crops face dry periods and fog is a common occurrence, especially during December, January, and February (Rahman et al 2018 , 2021b ; Ghafoor et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Moosavi et al [54] showed that the cultivation of cowpea with biochar enhanced the seed number per plant due to the relief of water-deficient stress and a higher phosphate and potassium content. Other studies also endorsed that biochar and nitrogen fertilizer improved the yield-related characteristics in arid climates [55,56]. On the basis of the findings from this study, it is recommended that the use of such soil conditioning materials is helpful for the sustainable production of crops in areas of limited water availability and could also be helpful for the community of the farmers for sustainable production under arid climatic conditions.…”
Section: Discussionmentioning
confidence: 56%
“…Grain weight decreased from control to HS and extended the HSd. This decrease in grain weight is due to the shrinking of grain fill duration with increasing temperature of 1-2 °C under the HS (Hussain et al, 2021). Losses in grain weight are obvious to limited grain fill duration with raised temperature (Narayanan, 2018).…”
Section: Quality Traitsmentioning
confidence: 96%